ARGUMENTASI PENGEMBALIAN GARIS-GARIS BESAR HALUAN NEGARA: ANALISIS KESINAMBUNGAN RENCANA PEMBANGUNAN JANGKA MENENGAH NASIONAL DALAM PERIODE 2005-2024 - Rahma, Anisa; Dennis, Brandon; Putra Noerrizky, Ivandy Arifin; George Edward, Nicolaas (Jurnal Politik Pemerintahan Dharma Praja, 2022)
The National Medium-Term Development Plan (RPJMN) has been critiqued for its continuity. Those critics became arguments on bringing back National Guidelines (GBHN) into Indonesian constitution. We analyze four RPJMN during the period 2005-2024 to observe its continuity. Analysis was made using the desk study method. By observing vision, mission, dan priority agendas of every RPJMN and also doing several case study, we found that it is true the there are discontinuity in RPJMN in particular, the ones made in respective to the governmental change from President Susilo Bambang Yudhoyono to President Joko Widodo. This discontinuity is indicated by the difference between priority agendas of the two RPJMNs in question. The result can be viewed as supporting pro GBHN arguments, but we think more representative thought process is needed for that matter.